UNVEILING OPHTHALMOLOGICAL FINDINGS IN CORNELIA DE LANGE SYNDROME: A RARE CASE REPORT - Dian Estu Yulia; Tan, Sabrina (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction: Cornelia de Lange syndrome (CdLS) is a rare congenital disorder with a distinctive combination of physical, cognitive, and behavioral features. This syndrome impacts multiple systems in the body, including the eyes. Case Report: A three-year-old boy with classic CdLS, emphasizing the ophthalmological findings of left eye ptosis, high myopia and astigmatism, microcornea, bilateral “dot opacities” cataracts, and tigroid fundus appearance. The patient was prescribed corrective eyeglasses to prevent amblyopia. Discussion: The clinical scoring system devised by the International CdLS Consensus Group aids in classifying CdLS cases into classic and non-classic variants, as well as guiding clinical genetic testing decisions. In all instances of suspected or confirmed CdLS, it is imperative that an ophthalmologist performs an initial eye examination promptly. Therefore, acquiring familiarity with the potential ophthalmological findings of CdLS is crucial. Common ocular presentations encompass features such as synophrys, thick eyebrows, long eyelashes, ptosis, myopia, microcornea, nasolacrimal duct obstruction, peripapillary pigment ring, and blepharitis. Meanwhile, less frequently encountered ocular manifestations include hyperopia and astigmatism, cataracts, microphalmia, glaucoma, optic nerve pallor and hypoplasia, nystagmus, and strabismus. Conclusion: Timely diagnosis, precise interventions, and regular ophthalmological monitoring are pivotal in preventing complications and enhancing visual function, thus improving the quality of life of individuals with CdLS.